XXth Century Man Czesław Miłosz With Opposing Aspect - Aybike KILIK (Ankara Üniversitesi Dil ve Tarih-Coğrafya Fakültesi Dergisi, 2017)
XXth century has become the age of scientific discoveries and social, cultural and political changes. While on the one half of the world democracy and capitalism were developing, on the other half totalitarian regimes like communism, fascism, Nazism were showing up. As a witness to all the chaos, pain and changes of that century, Czesław Miłosz was an artist who had so much to say. This article describes the perspective of Miłosz, who captures attention especially with the attitude to totalitarian regimes, on XXth century in light of his works and life story.